The Influence of Physical Fitness Test Towards Students’ Motivation in Learning Physical Education of Grade XI - Noviana Amelia; Simon Mulia (Bandar Lampung University (UBL), 2014)
Physical Education (PE) is critical to the development and maintenance of good health in students’ life. Therefore, Physical Fitness Components (PFC) that is trained through Physical Fitness Test (PFT) must be applied in the PE class because it leads and encourages students to live a healthy lifestyle. Unfortunately, the students in grade XI SMA ABC Tangerang, did not learn PFC and PFT. When it was time for PE class, the students also had low motivation to participate. This research is a quasi-experimental research that compared two groups of subjects:XI IPA boys (experimental group) and XI IPS boys (control group). The research was conducted in two meetings. The motivation has been measured by using questionnaire with high reliability (r=0.725) and in very high reliability (r=0,952). After tested the questionnaire result with t-test for independent samples, the result has showed that there is significant difference of motivation between the experimental group and the control group (p=0,000, p<0,05).